Morphological, molecular, and histopathological characterization of a new species of Henneguya infecting farmed Astyanax lacustris in Brazil - Margarido, Yvana M.M. [UNESP]; Adriano, Edson A.; Valladão, Gustavo M.R.; Naldoni, Juliana; Pilarski, Fabiana [UNESP] (Elsevier, 2021)
The present study describes the morphological, histopathological and SSU rDNA data of a new myxosporean species infecting farmed Astyanax lacustris fish from the state of São Paulo, Brazil. Henneguya lambariensis sp. nov. was found infecting the gills, and the plasmodial development resulted in displacement, blood congestion, compression, deformation and lamellar fusion, stretching of the epithelia, hyperplasia of the epithelial cells, edema, and mild infiltration of the mast cells and lymphocytes. The SSU rDNA sequencing resulted in the sequencing of 1804 nucleotides that did not correspond to any myxosporean sequences deposited in GenBank. The closest phylogenetic affinity of the new species was to the South American Henneguya loreotoensis and Henneguya guanduensis, which also parasite the gills. The present study suggests this new myxosporean species has considerable pathogenic potential, and health monitoring should be implemented in A. lacustris fish farms to ensure production.
Keywords: Aquaculture; Cnidaria; Host-parasite interaction; Myxosporea; Myxozoa; Phylogeny